2010
DOI: 10.1002/pi.2981
|View full text |Cite
|
Sign up to set email alerts
|

Self‐assembly and degradation of poly[(2‐methacryloyloxyethyl phosphorylcholine)‐block‐(D,L‐lactide)] diblock copolymers: large compound micelles to vesicles

Abstract: Biodegradable poly[(2‐methacryloyloxyethyl phosphorylcholine)‐block‐(D,L‐lactide)] (PMPC‐b‐PLA) diblock copolymers with various hydrophilic PMPC weight fractions (fPC) will spontaneously self‐assemble into well‐defined vesicles and large compound micelles (LCMs) in water. Transmission electron microscopy, scanning electron microscopy, dynamic light scattering and fluorescence microscopy were used to observe their aggregate morphologies. The degradation of the LCMs was investigated and the loss of molecular wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…The R g /R ho ratio values can give significant details about the morphology/structure of the formed nanostructures. As it is reported in the literature, the corresponding R g /R ho ratio values for spherical micellar structures (core-shell morphology) are in the range of 0.7-0.9, and for vesicular structures, they are in the range of 0.9-1.9 [70]. Therefore, the formed nanosized particles are expected to have spherical structures in the cases that the determined R g /R ho ratio values are close to 0.8 and maybe vesicular structures in the cases that the determined R g /R ho ratio values are above 0.9.…”
Section: Effects Of Temperature and Ph On The Self-assembly Behavior supporting
confidence: 66%
“…The R g /R ho ratio values can give significant details about the morphology/structure of the formed nanostructures. As it is reported in the literature, the corresponding R g /R ho ratio values for spherical micellar structures (core-shell morphology) are in the range of 0.7-0.9, and for vesicular structures, they are in the range of 0.9-1.9 [70]. Therefore, the formed nanosized particles are expected to have spherical structures in the cases that the determined R g /R ho ratio values are close to 0.8 and maybe vesicular structures in the cases that the determined R g /R ho ratio values are above 0.9.…”
Section: Effects Of Temperature and Ph On The Self-assembly Behavior supporting
confidence: 66%
“…Additionally, in Table , the length of the extended single copolymer chains is listed, which is apparently smaller than the determined size of PDMAEMA‐ b ‐PLMA aggregates (Table ). This fact indicates the existence of spherical supramolecular micellar aggregates, having not a simple core–shell structure but rather a compound micelle morphology . In previous work where amphiphilic block copolymers based on PLMA block were studied we reported the formation of compound micelles in aqueous solutions, due to the long aliphatic side chains of PLMA, which make difficult the organization of the PLMA blocks in small spherical cores .…”
Section: Resultsmentioning
confidence: 92%
“…These structures are expected to have a core–shell morphology since as temperature increases PNIPAM blocks become less hydrophilic and should occupy the inner part of the spherical structure/aggregate while the well solvated POEGA blocks should occupy the periphery. From the literature, R g / R h0 values in the range of 0.7–0.9 indicate spherical morphology and R g / R h values in the range of 0.9–1.9 indicate vesicular morphology …”
Section: Resultsmentioning
confidence: 99%
“…This observation indicates the hydrogen bonding between the carboxyl group of IND and amide group of PNIPAM block. Moreover, it is worth mentioning that in the spectrum of PNIPAM‐ b ‐POEGA‐2, the band at 1638 cm −1 was assigned to the carbonyl of amide group . It can be observed that in the spectra of copolymer/IND mixed aggregates, there is a small shift of the band attributed to the carbonyl group of amide group, most probably because of the intermolecular hydrogen bonding interactions between the carbonyl group of PNIPAM block and the hydroxyl group of IND.…”
Section: Resultsmentioning
confidence: 99%